2021
DOI: 10.1007/s11069-021-05057-1
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire impacts on education and healthcare: Paradise, California, after the Camp Fire

Abstract: The 2018 Camp Fire caused significant damages to the education and healthcare systems in the town of Paradise, CA. This paper presents the findings of a qualitative case study about disaster impacts and disparities, interdependencies, and recovery strategies of schools and hospitals in Paradise. Four major themes of findings emerged from the qualitative analysis of interviews with teachers, counselors, and administrators in Paradise education and healthcare systems and extensive archival research. First, compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…There are several reasons for this. First, regarding hospital resources, large-scale wildfires (even without a raging pandemic) could force local hospitals to be closed or evacuated due to electricity failure, water shortages in buildings, damaged infrastructure or disrupted transportation systems for the transfer of patients ( Hamideh et al, 2022 ; Melnychuk et al, 2022 ; Schranz et al, 2010 ). Wildfires can also rapidly increase demands on health resources such as ventilators, medical services, and extra care for patients with severe COVID-19 symptoms ( Ranney et al, 2020 ; Zangrillo et al, 2020 ).…”
Section: Prior Literature and Hypothesesmentioning
confidence: 99%
“…There are several reasons for this. First, regarding hospital resources, large-scale wildfires (even without a raging pandemic) could force local hospitals to be closed or evacuated due to electricity failure, water shortages in buildings, damaged infrastructure or disrupted transportation systems for the transfer of patients ( Hamideh et al, 2022 ; Melnychuk et al, 2022 ; Schranz et al, 2010 ). Wildfires can also rapidly increase demands on health resources such as ventilators, medical services, and extra care for patients with severe COVID-19 symptoms ( Ranney et al, 2020 ; Zangrillo et al, 2020 ).…”
Section: Prior Literature and Hypothesesmentioning
confidence: 99%
“…These groups also had limited access to recovery resources following the fires [5]. The Camp Wildfire of 2018 was also found to disproportionately impact certain socio-economic and demographic groups, particularly racial minorities, low-income individuals, and disabled individuals [7].…”
Section: Spatial Pattern Of California Wildfires and Socio-economic A...mentioning
confidence: 99%
“…Prior studies conducted on the potential association between wildfire risk and socio-economic-demographic characteristics focus primarily on the various human factors that generate unequal exposure and susceptibility to wildfires [3] [5]. Findings from these studies suggest that a positive association exists between wildfire hazard exposure and socio-economic disadvantage [6] [7]. Additionally, existing studies found that wildfire vulnerability is spread unequally across race and ethnicity, with census tracts that were majority Black, Hispanic or Native American experiencing much greater vulnerability to wildfire compared to other census tracts.…”
Section: Introductionmentioning
confidence: 99%
“…Wildfires often result in widespread destruction, including to the systems and infrastructure that support people's health and wellbeing. Previous research has documented the severe, lasting impacts of wildfires, and of disasters more broadly, affecting the social and economic infrastructure that support community health and wellbeing, including economic stability, education access and quality, healthcare access and quality, neighborhood and built environment, and social and community context [3,6,7]. Post-disaster impacts on one domain can compound negative impacts on others.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the destruction of local schools, this housing instability disrupts children's school attendance and eventual educational attainment [8]. The displacement of the limited local medical providers that a rural community had available pre-wildfire, as well as the destruction of local medical facilities, further curtail healthcare access [3,6]. Those with the least resources pre-disaster are the most likely to experience lasting disruptions to their economic stability, housing, education access, and other key social and economic resources that support wellbeing, exacerbating pre-disaster inequities [9].…”
Section: Introductionmentioning
confidence: 99%